An investigation on the techniques for inscribing Bragg grating structures - Ahmed Tahir, Bashir (National Institute of Research and Development for Optoelectronics, 2009)
This article describes the various techniques used in fabricating standard and complex Bragg grating structures in optical fibers. The objective here is to review a detailed outlook on the technology for writing fiber Bragg gratings. The fiber Bragg grating represents a periodic variation of the refractive index of the fiber core along the length of the fiber. Writing a fiber grating optically in the core of an optical fiber requires irradiating the core with a periodic interference pattern. Depending on the fabrication technique employed, Bragg gratings may be labeled as internally or externally written. Far more useful, Bragg gratings are inscribed using external techniques such as the interferometric, point-by-point and phase mask which overcome the fundamental limitation of internally written gratings. Although, these processes were initially considered difficult due to the requirements of submicron resolution and thus stability, today they are well controlled and the inscription of Bragg gratings using these techniques is considered routine. One of these methods (phase mask) has been used to fabricate the fiber Bragg gratings for optical sensing such as temperature and strain. The main aim of this article is to compare these methods and the selection of the optimal method for the fabrication of required fiber Bragg grating.